Selective glucocorticoid receptor-activating adjuvant therapy in cancer treatments - Sundahl, Nora (Oncoscience, 2016)
Although adverse effects and glucocorticoid resistance cripple their chronic use, glucocorticoids form the mainstay therapy for acute and chronic inflammatory disorders, and play an important role in treatment protocols of both lymphoid malignancies and as adjuvant to stimulate therapy tolerability in various solid tumors. Glucocorticoid binding to their designate glucocorticoid receptor (GR), sets off a plethora of cell-specific events including therapeutically desirable effects, such as cell death, as well as undesirable effects, including chemotherapy resistance, systemic side effects and glucocorticoid resistance. In this context, selective GR agonists and modulators (SEGRAMs) with a more restricted GR activity profile have been developed, holding promise for further clinical development in anti-inflammatory and potentially in cancer therapies. Thus far, the research into the prospective benefits of selective GR modulators in cancer therapy limped behind. Our review discusses how selective GR agonists and modulators could improve the therapy regimens for lymphoid malignancies, prostate or breast cancer. We summarize our current knowledge and look forward to where the field should move to in the future. Altogether, our review clarifies novel therapeutic perspectives in cancer modulation via selective GR targeting.